Genric Differentiation in the Relationship between L2 Vocabulary Knowledge and Writing Performance - Davoud Amini; Zahra Iravani (Journal of Modern Research in English Language Studies)
In cognitive process theories of L2 writing, the rich lexical knowledge plays a key role in facilitated writing performance. Therefore, the inquiry into the relationship between aspects of vocabulary knowledge and writing performance can proffer theoretical clues on L2 writing process. However, assessing and researching writing is not independent from the type of tasks or genres that are used for eliciting samples of writing. Accordingly, this study probed into the association between vocabulary knowledge and L2 writing performance with a focus on possible differences originating from descriptive and narrative genres of writing. Four distinctive writing tasks were given to 101 Iranian advanced-level EFL learners whose depth and breadth of vocabulary knowledge were measured with Word Associates Test and New Vocabulary Levels Test. The analyses indicated moderate positive correlations between depth and breadth of vocabulary knowledge and writing performance in both descriptive and narrative genres. Moreover, the results of regression analysis revealed a significant positive predictive power for both depth and breadth in descriptive and narrative writings. Also, Iranian EFL learners performed better on descriptive writing than narrative writing. Genric differentiations in the relationship between lexical knowledge and L2 writing performance seem to be mediated by such factors as learners’ proficiency level and L1 cultural background. However, achieving an overarching view of the genric differentiations in affecting the relationship between EFL learners’ vocabulary knowledge and writing performance awaits further complementary research with a focus on all genres of writing while the multidimensionality of L2 vocabulary knowledge is taken into account.